EFFICACY OF ABATACEPT IN A PATIENT WITH POLYARTICULAR JUVENILE IDIOPATHIC ARTHRITIS REFRACTORY TO TNF-α - Yu. M. Spivakovskii; Yu. V. Chernenkov; A. Yu. Spivakovskaya; O. V. Skupova; E. N. Shul'gina (Вопросы современной педиатрии)
The article describes the experience of the application of genetically engineered biological drug and an inhibitor of T lymphocyte costimulation – abatacept – at a standard dose in a child with polyarticular juvenile idiopathic arthritis. The disease was characterized by the development of uveitis, as well as the ineffectiveness of two inhibitors of tumour necrosis factor α treatment. Successful relief of acute inflammatory reaction of the joints on the background of the normalization of laboratory indicators of disease severity in the application of abatacept in combination with methotrexate was detected. The study gave the characteristics of the dynamics of clinical recovery of the patient and described the dynamic changes of clinical and laboratory symptoms. A steady improvement of the child under nine-month follow-up on the background of the selected scheme basic anti-inflammatory therapy should be noted.